2019
DOI: 10.1097/01.hs9.0000561636.42487.8d
|View full text |Cite
|
Sign up to set email alerts
|

S839 phase Ii Study of Oral Rigosertib Combined With Azacitidine in Patients With Higher‐risk Myelodysplastic Syndromes (Mds)

Abstract: Background: Azacitidine based combination trials have not demonstrated improved response or outcome over single agent azacitidine (Sekeres JCO 2017; Ades ASH 2018). Results of a Phase I/II study in MDS patients demonstrated oral rigosertib and standard-dose azacitidine to be well-tolerated with efficacy in HMA-naive and HMA-failure patients: at 560 mg qAM/280 mg qPM rigosertib dosing, overall response rate (ORR) was 77%; 88% for HMA-naive group, 60% for HMA-failure group. An increase in genitourinary (GU) adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Of the 55 patients evaluable for response, median duration of response was 12.2 months in HMAnaïve patients and 10.8 months in HMA-failure patients. 16 Responses to treatment occurred in all IPSS-R subgroups. In the low/intermediate-risk subgroup (n = 17), complete response (CR) occurred in 4 patients and marrow CR (mCR) occurred in 5 patients.…”
Section: Emerging and Investigational Therapies In Mdsmentioning
confidence: 95%
See 3 more Smart Citations
“…Of the 55 patients evaluable for response, median duration of response was 12.2 months in HMAnaïve patients and 10.8 months in HMA-failure patients. 16 Responses to treatment occurred in all IPSS-R subgroups. In the low/intermediate-risk subgroup (n = 17), complete response (CR) occurred in 4 patients and marrow CR (mCR) occurred in 5 patients.…”
Section: Emerging and Investigational Therapies In Mdsmentioning
confidence: 95%
“…The 5-year OS did not differ significantly between groups: 94.7% vs 95.9% in the 9-week and 12-month groups, respectively (HR,1.36 90% CI, 0.98-1.89). 16 (Table 2) Of these 5 trials, only PERSPEHONE's results showed noninferiority. In a meta-analysis of the 5 trials, there was a statistically significant difference in the DFS and OS between the shorter duration of treatment-both 9 weeks and 6 months, pooled-compared with the 12-month duration of treatment, with a HR of 1.21 (95% CI, 1.08-1.37) for DFS and an HR of 1.31 (95% CI, 1.08-1.59) for OS.…”
Section: Examining the Evidence: 1 Year Of Trastuzumab Vs A Shorter Dmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5-year OS did not differ significantly between groups: 94.7% vs 95.9% in the 9-week and 12-month groups, respectively (HR,1.36 90% CI, 0.98-1.89). 16 (Table 2)…”
Section: Examining the Evidence: 1 Year Of Trastuzumab Vs A Shorter Durationmentioning
confidence: 99%